The evolving landscape of biomarker testing for non-small cell lung cancer in Europe - Kerr, Keith M; Bibeau, Frédéric; Thunnissen, Erik; Botling, Johan; Ryška, Aleš; Wolf, Jürgen; Öhrling, Katarina; Burdon, Peter; Malapelle, Umberto; Büttner, Reinhard (Lung cancer (Amsterdam, Netherlands), 2021)
The discovery of oncogenic driver mutations rendering non-small cell lung cancer (NSCLC) targetable by small-molecule inhibitors, and the development of immunotherapies, have revolutionised NSCLC treatment. Today, instead of non-selective chemotherapies, all patients with advanced NSCLC eligible for treatment (and increasing numbers with earlier, less extensive disease) require fast and comprehensive screening of biomarkers for first-line patient selection for targeted therapy, chemotherapy, or immunotherapy (with or without chemotherapy). To avoid unnecessary re-biopsies, biomarker screening before first-line treatment should also include markers that are actionable from second-line onwards; PD-L1 expression testing is also mandatory before initiating treatment. Population differences exist in the frequency of oncogenic driver mutations: EGFR mutations are more frequent in Asia than Europe, whereas the converse is true for KRAS mutations. In addition to approved first-line therapies, a number of emerging therapies are being investigated in clinical trials. Guidelines for biomarker testing vary by country, with the number of actionable targets and the requirement for extensive molecular screening strategies expected to increase. To meet diagnostic demands, rapid screening technologies for single-driver mutations have been implemented. Improvements in DNA- and RNA-based next-generation sequencing technologies enable analysis of a group of genes in one assay; however, turnaround times remain relatively long. Consequently, rapid screening technologies are being implemented alongside next-generation sequencing. Further challenges in the evolving landscape of biomarker testing in NSCLC are actionable primary and secondary resistance mechanisms to targeted therapies. Therefore, comprehensive testing on re-biopsies, collected at the time of disease progression, in combination with testing of circulating tumour DNA may provide important information to guide second- or third-line therapies. Furthermore, longitudinal biomarker testing can provide insights into tumour evolution and heterogeneity during the course of the disease. We summarise best practice strategies for Europe in the changing landscape of biomarker testing at diagnosis and during treatment.
Keywords: NSCLC; Europe; Next-generation sequencing; Asie; Evropa; nádory plic; mutace; Biomarkers, Tumor; Predictive molecular pathology; nemalobuněčný karcinom plic; nádorové biomarkery; Mutation; Humans; Oncogenic driver mutations; Carcinoma, Non-Small-Cell Lung; Asia; Precision medicine; Targeted therapies; Lung Neoplasms; lidé